2022
DOI: 10.1097/bpo.0000000000002163
|View full text |Cite
|
Sign up to set email alerts
|

When Will You Succeed Casting Patients With Early-onset Scoliosis? Prospective Evaluation of Predictive Radiographic Parameters

Abstract: Background: In a recent retrospective study, in cast correction of the major curve correlated with final curve size in patients with early-onset scoliosis treated with casting. We therefore sought to perform a prospective study with controlled methodology to determine if there are parameters associated with reduction of coronal deformity. Methods: A prospective, observational study was conducted between 2014 and 2019 at selected sites willing to comply with a standard radiographic and follow-up protocol. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In a multicenter, retrospective study, Fedorak et al [12] found that children who underwent casting prior to 18 months of age were more likely to have a major curve of less than 15° at a minimum 2-year follow-up after casting. Glotzbecker et al found similar results [13]. While recognizing the importance of early detection and treatment, other authors have highlighted the risk of over treatment, arising the doubt of how many of these patients could have experienced spontaneous resolution without any treatment [14].…”
Section: Treatmentmentioning
confidence: 86%
“…In a multicenter, retrospective study, Fedorak et al [12] found that children who underwent casting prior to 18 months of age were more likely to have a major curve of less than 15° at a minimum 2-year follow-up after casting. Glotzbecker et al found similar results [13]. While recognizing the importance of early detection and treatment, other authors have highlighted the risk of over treatment, arising the doubt of how many of these patients could have experienced spontaneous resolution without any treatment [14].…”
Section: Treatmentmentioning
confidence: 86%